Economic evaluation of projects in the electricity supply industry - Khatib, Hisham 1936- (The Institution of Engineering and Technology, 2014)
The book reviews development in the following fields: global electrical power planning; electrical power investments; electrical power projects; projects financial evaluation; discounting; projects economic evaluation; environmental considerations; cost estimation; electricity generation in a carbon-constrained world; power supply reliability; electricity trading; investment projects analysis; electricity sector; risk management; and electricity markets.